Pityriasis rubra pilaris type III classic juvenile. - Milano, A. (European Journal of Pediatric Dermatology, 2012)
A 15-year-old girl was first observed for the presence of erythematous and scaling lesions with clear-cut borders on the neck, décolleté and retro-auricular regions, palmoplantar keratoderma of yellow-orange color and keratotic follicular papules tending to get confluent on the abdomen and limbs, saving antecubital folds and front surface of the thighs (Fig. 1, 2, 3). The personal and family history was negative for major diseases. The skin lesions, which had begun about two years ago on palms and soles, gradually spread to most of skin area. The patient complained of itching and reported an improvement in the summer. The clinical diagnosis was pityriasis rubra pilaris type III (classic juvenile). Oral therapy with acitretin (0.45 mg/kg per day) and topical corticosteroids were prescribed. After 45 days there was a marked improvement of the clinical picture.